Precipitation of gold in rich clarified solution with aluminum in Barrick mining - Villavicencio, Edwar Villavicencio (2014)
Barrick Misquichilca mining company - Pierina Unit, in the process of closure is finding optimal processes, which will improve performance at low cost and with the less environmental impact. In this context, aluminum is evaluated to replacement zinc in the Merrill Crowe process, a series of experimental tests were conducted and it was determined that it is not necessary the presence of neither free cyanide nor vacuum pump for the reaction to occur. All information obtained was analyzed and processed, the results show consistent, representative values and reported good results. The best result was obtained at pH 11.5, an addition of aluminum powder of 0.25 g / l (55 kg for a flow of 220 m3 / h) without deaeration, with 0.023 ppm and 0.041 ppm of silver and gold grades in the Barren solution respectively.